2017
DOI: 10.1515/jpm-2017-0189
|View full text |Cite
|
Sign up to set email alerts
|

Expectant management of caesarean scar ectopic pregnancy: a systematic review

Abstract: Caution should be exercised when choosing expectant management in cases of viable CSPs, and if chosen, the patient should be counselled adequately for possible outcomes including loss of pregnancy and hysterectomy. Expectant management is acceptable in CSPs with no foetal cardiac activity. There is a need for prospective research on this topic with adequate reporting on possible prognostic markers, as well as a need to improve on the techniques to prevent loss of fertility during delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 23 publications
0
29
0
Order By: Relevance
“…Expectant management is an acceptable option in non-viable CSP’s and it may also be discussed in cases that appear to grow inwards, however following extensive counselling regarding the associated risks [4]. A recent systematic review of 56 cases of CSP found that live births were achieved in 73% of the cases and 25% of them were preterm [13]. In addition, more than half of cases with no fetal cardiac activity resolved during expectant management, but high (70%) rates of hysterectomy were reported overall [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Expectant management is an acceptable option in non-viable CSP’s and it may also be discussed in cases that appear to grow inwards, however following extensive counselling regarding the associated risks [4]. A recent systematic review of 56 cases of CSP found that live births were achieved in 73% of the cases and 25% of them were preterm [13]. In addition, more than half of cases with no fetal cardiac activity resolved during expectant management, but high (70%) rates of hysterectomy were reported overall [13].…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review of 56 cases of CSP found that live births were achieved in 73% of the cases and 25% of them were preterm [13]. In addition, more than half of cases with no fetal cardiac activity resolved during expectant management, but high (70%) rates of hysterectomy were reported overall [13]. Another meta-analysis concluded that, in cases of CSPs with fetal heart activity, expectant management is associated with a high risk of maternal morbidity, whereas it may be a reasonable option in cases with no cardiac activity [3].…”
Section: Discussionmentioning
confidence: 99%
“…Even though expectant management of CSEP has been described [2,3,15,18], the safety of continuing pregnancy is questionable. Caution must be exercised when choosing expectant management in cases of viable CSEP as it carries a significant risk of complications, including uterine rupture, severe haemorrhage and hysterectomy [4,18,19]. In a systematic review of a total of 56 cases (including 44 cases with fetal cardiac activity) of CSEP managed expectantly, live births were achieved in 73% with a very high hysterectomy rate of 70% [18].…”
Section: Expectant Managementmentioning
confidence: 99%
“…Caution must be exercised when choosing expectant management in cases of viable CSEP as it carries a significant risk of complications, including uterine rupture, severe haemorrhage and hysterectomy [4,18,19]. In a systematic review of a total of 56 cases (including 44 cases with fetal cardiac activity) of CSEP managed expectantly, live births were achieved in 73% with a very high hysterectomy rate of 70% [18]. Women with viable CSEP and relatively favourable findings on imaging such as endogenic type, COS-2 on ultrasound and residual myometrial thickness of >5 mm on MRI may continue with the pregnancy if they have a strong desire to do so [19].…”
Section: Expectant Managementmentioning
confidence: 99%
See 1 more Smart Citation